HUBUNGAN ANTARA HIPERTENSI DENGAN KEJADIAN STROK ISKEMIK DI BANGSAL DAN POLIKLINIK SARAF RSUD DR. SOEDARSO PONTIANAK - ., Agus Darmanto (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Stroke is one of the causes of death and major neurologicaldisability in Indonesia with a comparison between disability and death isfour to one. Cases of stroke in doctor Soedarso General HospitalPontianak is increase every year. Hypertension is often found in patientswith ischemic stroke and hypertension cases are still high in doctorSoedarso General Hospital Pontianak. Objective: This study aimed todetermine the relationship of hypertension to the incidence of ischemicstroke in neurological ward and clinic doctor Soedarso General HospitalPontianak. Methodology: This study was a descriptive analytic study withcase-control study design. The study was conducted in doctor SoedarsoGeneral Hospital Pontianak. This cases meet the criteria retrospectivelystudied using data obtained from interviews and medical records. Theresults were tested by chi-square statistical test with SPSS 20.0. Results:From the statistical analysis of values obtained significancy is 0.005 (p<0,05). It was claimed that there was a relationship between hypertensionwith ischemic stroke. In addition, the obtained value of odds ratio (OR) is4.59. Conclusion: Hypertension was a risk factor for ischemic stroke.Hypertensive patients at risk of having an ischemic stroke 4.59 timesgreater than the subjects who did not suffer hypertension.Keywords: Hypertension, Ischemic Stroke, doctor Soedarso GeneralHospital Pontianak